Dielectric Strength Improvement Of Natural Ester Insulation Oil:Optimization Of Mixed Antioxidants Via Two-Level Factorial Design - Sharin, Ab Ghani (Asian Research Publishing Network (ARPN), 2016)

(untitled)
Recent studies have shown that the addition of selected antioxidants into mineral oils or natural ester insulation (NEI) oils have improves the AC breakdown voltage (BdV), viscosity,flash point and fire point of these oils.The results of previous studies show that the addition of propyl gallate (PG) and citric acid (CA) antioxidants increases the AC BdV of NEI oils.However,previous researchers have implemented one-factor-at-a-time (OFAT) method as their experimental design approach and they overlooked the possibility through combination of antioxidants at optimum ratios that will yield a better result.In addition,a large number of test runs are required to investigate the effect of these antioxidant mixtures on the performance of insulation oils.Hence,in this study,two-level (2k) factorial design of experiments is used to determine the optimum concentration of PG and CA which will maximize the AC BdV of NEI oil.The results show that the optimum concentration of PG and CA that yields the highest AC BdV of NEI oils is 0.05 and 0.25 wt.%, respectively.A regression model is also developed to predict the AC BdV of NEI oils as a function of PG and CA concentrations.